Dehydration diffusion of B(OH)4-sodalite investigated by micro-Raman spectroscopy on single crystals and combined TG/IR on powders - Rüscher, Claus H.; Kiesel, Florian; Wollbrink, Alexander; Schomborg, Lars; Buhl, Josef-Christian (Diffusion Fundamentals, 2016)
Dehydration experiments were carried out on larger B(OH)4-sodalite single crystals, Na8[Al6Si6O24](B(OH)4)2, at temperatures 300°C, 350°C and 400°C. Profiles of relative intensity variations of B-(OH)/Si-O vibration could be measured by micro-Raman spectroscopy ranging typically between 5 and 40 μm into the interior of the crystals. Profile analyses reveal effective dehydration diffusion coefficients DOH between 10-11 and 10-9 cm2/s with an Arrhenius activation energy Ea ≈ 1.3 eV. H/D exchange experiments were realized at temperatures 50, 100 and 150°C in closed tubes. Profiles of OD/OH Raman intensities reveal effective H/D exchange diffusion coefficients DHD between 1.5∙10-10 and 4∙10-11 cm2/s with Ea ≈ 0.4 eV. The dehydration effect for crystalline powders was reinvestigated up to 500°C in TG experiments and by IR spectra. These data show that dehydration takes place forming NaBO(OH)2- and NaBO2-sodalite centered at temperatures 250°C and 410°C, respectively. It is discussed that diffusion coefficients DP could be estimated using the mass losses for the two stages of dehydration related to the experiments on the polycrystalline samples. Linear extrapolation of DOH, i.e. the diffusion coefficients obtained on larger single crystals, towards lower temperature well approximates DP using the dehydration effect obtained for crystalline powders between 140 and 180°C assuming spherical crystals of 0.1 μm diameters. H/D exchange could occur with proton/deuteron jumps through the four-ring windows of the sodalite framework. Larger ions or molecules predominantly pass through the six-ring windows which requires window opening.